(untitled) (African Multidisciplinary Journal of Research, 2025)
This study examined the influence of financial incentives on youth participation in the gig economy in Embakasi Sub-County, Nairobi County, Kenya. As flexible employment arrangements gain traction, the gig economy offers young people immediate income opportunities and adaptable work schedules. However, the trade-off includes inconsistent earnings and limited access to social protection. Using a cross-sectional mixed-methods design, the study combined survey data from 399 youth respondents and key informant interviews from major stakeholders such as Uber, Glovo, Bolt, and government agencies. Findings indicated that 39.7% of respondents rely on gig work as their primary income source. Nearly half (47%) reported that gig earnings were higher than traditional employment, and 50.5% describe their income as consistent to some degree. However, 44.4% noted that they struggle to meet financial obligations during slow periods, and 57.5% cannot access health insurance through their gig income. Although 65.4% manage to save for emergencies, concerns over unpredictable income remain a key challenge. The study employed both descriptive and inferential statistics, revealing significant relationships between gig work participation and variables such as income consistency (p=.000), financial resilience during slow periods (p=.002), and motivation for professional development (p=.009). Qualitative findings reinforced the appeal of quick payouts and low entry barriers but also underscored concerns about long-term security, rising costs, and inadequate social protections. The research concluded that financial incentives play a dominant role in youth participation in the gig economy, driven by immediate income and flexible work structures. However, sustainable engagement will require targeted reforms, including income guarantees, social safety nets, and financial literacy initiatives. The findings offer valuable insights for policymakers and platform operators to align gig economy structures with the socio-economic realities of the urban youth